\left\{ \begin{array} { l } { a + b + c = - 2 } \\ { a - b + c = 20 } \\ { \frac { 9 } { 4 } a + \frac { 3 } { 2 } b + c = \frac { a } { 9 } + \frac { b } { 3 } + c } \end{array} \right.
Solve for a, b, c
a=6
b=-11
c=3
Share
Copied to clipboard
a+b+c=-2 a-b+c=20 81a+54b+36c=4a+12b+36c
Multiply each equation by the least common multiple of denominators in it. Simplify.
a=-b-c-2
Solve a+b+c=-2 for a.
-b-c-2-b+c=20 81\left(-b-c-2\right)+54b+36c=4\left(-b-c-2\right)+12b+36c
Substitute -b-c-2 for a in the second and third equation.
b=-11 c=-2-\frac{5}{11}b
Solve these equations for b and c respectively.
c=-2-\frac{5}{11}\left(-11\right)
Substitute -11 for b in the equation c=-2-\frac{5}{11}b.
c=3
Calculate c from c=-2-\frac{5}{11}\left(-11\right).
a=-\left(-11\right)-3-2
Substitute -11 for b and 3 for c in the equation a=-b-c-2.
a=6
Calculate a from a=-\left(-11\right)-3-2.
a=6 b=-11 c=3
The system is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}